Respon Pertumbuhan Padi (Oryza Sativa L.) Terhadap Interval Waktu Penyiraman dengan Pemberian Asam Salisilat - Delawanti Puspita; Melfa Aisyah Hutasuhut; Khairunnisa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the effect of irrigation intervals and salicylic acid application on the growth of rice (Oryza sativa L.) under drought stress conditions. This study used a factorial Randomized Block Design (RBD) with 3 replications, consisting of two treatment factors: the first factor was irrigation interval (every 2 days, 4 days, and 6 days) and the second factor was salicylic acid concentration (0 mM, 1 mM, and 2 mM); observations were made on stomatal density, chlorophyll a content, and chlorophyll b content using spectrophotometric methods, with data analyzed using analysis of variance (ANOVA) and, where significantly different, followed by Duncan's Multiple Range Test (DMRT) at α = 5% significance level. The results showed that the irrigation interval had a significant effect on stomatal density with the best treatment at a 6-day interval, chlorophyll a content was significantly affected by irrigation interval and the interaction between irrigation interval and salicylic acid application, and chlorophyll b content was significantly affected by salicylic acid application and the interaction between irrigation interval and salicylic acid application. This study concludes that irrigation intervals and salicylic acid application, both independently and in combination, significantly affect the physiological responses of rice plants, indicating that salicylic acid has potential as a drought stress tolerance-enhancing agent in rice. Keywords: Salicylic Acid, Rice (Oryza sativa L.), Watering.